Musykilât Ta’lîm Al-Lughah Al-Arabiyyah fî Tanmiyah Mahârah Al-Kalâm ladâ Ath-Tholibât At-Takhassus fî Ma’had Al-Qur’ân Hidayah Ar-Rahman Bogor - Aini Nur Sholehah; Syirojul Huda Ma’mun (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
يهدف هذا البحث لوصف تعليم اللغة العربية ومعرفة المشكلات حول تعليم اللغة العربية لدى المبتدئين. هذا بحث ميداني، المدخل الذي سلكته الباحثة في هذا البحث هو المدخل الكيفي. والأسلوب المستخدم هو الأسلوب الوصفي التحليلي. أما طريقة في تحليل البيانات تعتمد الباحثة على طريقة ميلز وهو برمان (Miles &Hubermen) وهي: جمع البيانات، ثم تصنيف البيانات وعرضها، ثم أخذ الاستنباط والتحقيق. تنقسم مشكلات تعليم اللغة العربية إلى أربعة أمور: الأول العامل اللغوي يتضمن من نظام قواعد الصوت،و قواعد اللغة، واجتماع المفردات، وترتيب الكلمات. الثاني العامل غير اللغوي يتضمن من الدوافع وميول تعليم الطلاب، كفاءة المعلم، وطريقة التدريس المستخدمة، الوقت المتاح. الثالث العامل النفسي والرابع العامل الاجتماعي ويتضمن منه الحضارة و عوامل البيئة الاجتماعية The research was purposed to describe the teaching of Arabic and to know the problems of teaching Arabic for the beginners. The research was qualitative. The method of this research was descriptive analytical method. The researcher used interview, observation, and documentation methods to collect the data, by using the Mills & Hubermen method to analyze the data. It consists of data collection, classification, presentation and conclusions. Problems in learning Arabic are divided into four factors. The first is linguistic problems including sound system, grammatic, vocabulary, and semantics. The Second is non-linguistic factors resulting from lack of motivation in teaching Arabic, instructional tools, teacher competence, learning strategies, inadequate time allocation, and textbooks. The third is social and psychological factors. The fourth is social factor includes culture, and social environment factors.